PENINGKATAN HASIL BELAJAR SISWA KELAS XA MAN 1 BANJARMASIN MELALUI PENERAPAN MODEL KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION PADA KONSEP REAKSI REDUKSI –OKSIDASI - Zahara, Rita (Jurnal PTK dan Pendidikan, 2018)
Research?s aim is to improve the student?s learning outcomes by using cooperative learning type Team Assisted Individualization (TAI) in reaction oxidation-reduction concept. This study used class action researched method with cycle model. The research was done in XA class of MAN 1 Banjarmasin with 36 students in 2014/2015 academic year. The research instrument was learning outcomes test, the teacher and student?s observation sheet, and the students?s response questionnaire. The data were the result of student?s learning outcome, the result of teacher and student?s observation, and student?s response to the study, then it was analyzed by qualitative descriptive. The results showed that by using TAI mode in reaction-oxidation-reduction concept could increase student?s learning outcomes, from grade 67,78 (38,88% ) in cycle I to grade 83,42 (78%) in cycle II.